"Hipertensão: eu aprendi a viver com ela" - relatos do saber construído como emancipação dos sujeitos - Silva, Fernanda Machado da (2010)
Systemic Arterial Hypertension (SAH) is presented as an important problem of public health, in the national and world scenery, for its epidemiologic and social relevance, evidenced by the high prevalence, by the indexes of mortality and by the fragility in the life of its bearers. Among the public policies for the SAH control, the education in health has been pointed out as a tool for social health promotion. Lined in the health promotion, the educational process in health, as a social practice, brings up a concern with the emancipation development of the subjects faced with the health/disease/care, in an individual and collective environment. It is a qualitative research, of the observational and descriptive type, whose objective was to know how the education in health influences in the lives of bearers of SAH, accompanied by a family health team. For the data collecting a semi-structured interview, document observation and analysis, in the period from February to August 2009 were used. Nine people bearers of SAH participated in the research, accompanied by Urlandia Family Health Team. The data underwent the theme analysis proposed by Minayo, from which four analytical categories emerged. It was observed that the interview, carried out in the home environment, enabled a moment of reflection to the subjects, what allowed that they reassessed and re-elaborated their conceptions about the meaning of the SAH and how they manage their lives towards the chronicity . This reflection was permeated by the way they noticed or experienced the health/disease/care process, lined in their life experiences in the social-cultural context to which they belong. Thus, it was evidenced that it pervaded in the speeches of the subjects the reflexes of their own health education, in relation to what they understand, how they live and manage their lives, in the living with SAH. With that, this study revealed that the repercussion of education in health, in the lives of these people, was intimately articulated with their conceptions and attitudes about this action and with the position taken by them towards their health/disease/care process. It is understood, thus, that the knowledge in health, built in the education actions in health represents the first step in the emancipation process of the subjects.